Countermeasures in information security and cybernetic vulnerability: empirical evidence of Brazilian companies (Revista de Administração, 2013)
Recently, a series of cyber attacks to firms and governments, in Brazil and abroad highlighted the potential economic impact of this kind of activity, from private and public perspectives. There is a vast economic literature - theoretical and empirical - that evaluates the incentives for the adoption of measures of information security. The current study developed an empirical evaluation of this phenomenon in Brazil. Logit and ordered probit models were to evaluate the effects on the probability of occurrence of information security problems, considering firms' characteristics, including measures of information security. Results indicate that there is a positive correlation between measures of information security and the probability of identifying the occurrence of cyber attacks, what suggests that the sophistication of these measures of protection increase the probability of identification of the problems.